Effects of plyometric training on explosive strength of lower limb for young athletes - Lu, D. (International Conference on Education, Management and Computing Technology (ICEMCT-15), 2015)
In this paper, 10 volleyball young athletes and 10 badminton young athletes were selected as the object of study, randomly dividing into control group and experimental group. The normal strength training was used in control group and plyometric training was used in experimental group. After eight weeks, the results show that firstly, plyometric training significantly improved the explosive effect of lower limbs for young athletes, especially on the indicators of vertical jump to touch and single vertical jump; secondly, plyometric training cannot significantly improve biggest strength of lower limbs for young athletes. It also indicates that the improvement of explosive power of lower limbs does not depend on the improvement of biggest strength of lower limbs for young athletes. The normal strength training is better than plyometric training for biggest strength training for young athletes. Therefore, we suggest that the plyometric training for young athletes should be gradual and limited load. There is a difference between young and adult athletes for the intensity and measurement of plyometric training that will not take adverse reactions in the body for young athletes.